Cerebral venous sinus thrombosis secondary to acute viral meningitis from cytomegalovirus and Epstein-Barr virus in immunocompetent patients: a case report - Amon-Tanoh, Muriel; Magala, Gloire Chubaka; Offoumou, Fiacre Delors; Kadjo, Cédric Valery; Aka, Arlette Désirée; Kouassi, Roseline Mohou Felandine; Tanoh, Abel Christian (International Journal of Research in Medical Sciences, 2024)
Cerebral venous sinus thrombosis (CVST) represents about 0.5% to 3% of all stroke cases, with a higher prevalence among younger populations. The estimated incidence is around 3 to 4 cases per million in adults and 7 cases per million in children. In tropical areas, there is often a notable association between infectious diseases and strokes. In sub-Saharan Africa, infections are identified as significant risk factors for cerebral venous thrombosis. Human cytomegalovirus (CMV) and Epstein-Barr virus (EBV), both ubiquitous members of the herpesvirus family, are typically asymptomatic; however, they can, in certain instances, contribute to the development of thromboembolic diseases (TED), particularly in immunocompromised individuals. The incidence of CVST linked to CMV or EBV in immunocompetent individuals without other risk factors is uncommon. This study presents two cases: the first involves a 15-year-old immunocompetent adolescent who experienced a rapid decline in alertness, while the second case pertains to a 43-year-old man who presented with sudden-onset headaches. Magnetic resonance venography (MRV) revealed extensive CVST on the left side in the first case and a sub occlusion of the left transverse sinus in the second. Analysis of cerebrospinal fluid isolated EBV and CMV through PCR, with positive serological results. The clinical outcome was favorable due to anticoagulant treatment combined with symptomatic management of the infections. The risk of CVST should not be overlooked in patients with symptoms related to CMV and EBV infection regardless of immune status and MRV should be considered to rule out this possibility.